A Framework to Assess Natural Chloride Background in Coastal Aquifers Affected by Seawater Intrusion in Eastern Spain. - Grima-Olmedo, Juan; Ballesteros-Navarro, Bruno; Pulido-Velazquez, David; Renau-Pruñonosa, Arianna; Alcalá, Francisco Javier; Llopis-Albert, Carlos; Jiménez-Gavilán, Pablo; Milkov-Ivanov, Nikolay; Baena-Ruiz, Leticia; Grima-Olmedo, Carlos; Milkov-Ivanov, Nikolay (MDPI, 2023)
The protection of groundwater resources in coastal aquifers is an increasingly important issue worldwide. To establish threshold values and remediation objectives, it is essential to know the natural background concentrations of relevant ions in groundwater. The rationale is to define the Natural Background Level (NBL) of chemical species determined by atmospheric and lithological forces. In many coastal aquifers, this evaluation worsens since atmospheric and lithological salinity combines with many other anthropogenic sources of salinity, including exogenous salinity induced by seawater intrusion (SWI). This paper presents a combination of six well-known statistical techniques and a new methodology (i.e., SITE index) in eight GWBs affected by SWI in Eastern Spain. The chloride ion was the selected conservative chemical specie to assess the qualitative status due to the variable SWI affection. The Natural Chloride Background (NCB) obtained from these methodologies at the GWB scale was compared with regional NCB data calculated with the Atmospheric Chloride Mass Balance (CMB) method in Continental Spain. The CMB method provides atmospherically derived NCB data that are not influenced by SWI or anthropogenic activities or lithological forces. This external evaluation can be considered the atmospheric fraction of NCB, which serves as a regional criterion to validate the more detailed statistical methodologies applied at the GWB scale. As a result, a conceptualization of NCB is obtained by means of a range of values between 115 mg L􀀀1 and 261 mg L􀀀1 in the studied coastal GWBs affected by SWI in Eastern Spain.
Keywords: Acuíferos - Mediterráneo; Aguas subterráneas - Protección; Groundwater; Chloride; Natural background; Coastal aquifers; Seawater intrusion; Eastern Spain